2016
DOI: 10.20452/pamw.3461
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the thickness of bronchial wall layers, emphysema score, and markers of remodeling in bronchoalveolar lavage fluid in patients with chronic obstructive pulmonary disease

Abstract: KEY WORDSchronic obstructive pulmonary disease, computed tomography, emphysema score, endobronchial ultrasound, markers of remodelling ABSTRACT INTRODUCTION Airway remodeling plays an important role in the development of chronic obstructive pulmonary disease (COPD). Imaging methods, such as computed tomography (CT) and endobronchial ultrasound (EBUS), may be useful in the assessment of structural alterations in the lungs.OBJECTIVES The aim of this study was to evaluate a relationship between the severity of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 5 publications
2
12
0
2
Order By: Relevance
“…We compared CT‐derived dimensions of proximal and distal airways, and measured low‐attenuation lung area (LAA%) by the conventional threshold level of −950 Hounsfield units, to show which of those indices correlate best with lung function, histology, and asthma biomarkers. The LAA% determines the percentile quantity of voxels showing a value lower than preset attenuation from all voxels within lung tissue and is usually employed for evaluation of emphysema . In asthma, however, it might be also related to the excessive narrowing of large and small airways with subsequent air trapping and hyperinflation .…”
Section: Introductionmentioning
confidence: 99%
“…We compared CT‐derived dimensions of proximal and distal airways, and measured low‐attenuation lung area (LAA%) by the conventional threshold level of −950 Hounsfield units, to show which of those indices correlate best with lung function, histology, and asthma biomarkers. The LAA% determines the percentile quantity of voxels showing a value lower than preset attenuation from all voxels within lung tissue and is usually employed for evaluation of emphysema . In asthma, however, it might be also related to the excessive narrowing of large and small airways with subsequent air trapping and hyperinflation .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation and bronchial wall remodeling can alter the anatomy and mechanical properties of the airways. In routine diagnosis, an assessment of tissue remodeling is commonly performed by morphometry and histopathological analysis of biopsies and/or high‐resolution computed tomography, endobronchial ultrasound,, or optical coherence tomography . However, new emerging approaches are strongly needed to help diagnosis of asthma.…”
Section: Introductionmentioning
confidence: 99%
“…10 The authors used both EBUS and HRCT to correlate the airway wall structural parameters as well as the so called emphysema score with the levels of selected biomarkers in the bronchoalveolar lavage fluid (BALF) and pulmonary function assessed in spirometry and body plethysmography. The evaluated biomarkers included matrix Although numerous antitobacco campaigns resulted in a decreased prevalence of some smoking--related diseases, chronic obstructive pulmonary disease (COPD), for which smoking remains the main risk factor, is still a major health problem worldwide.…”
mentioning
confidence: 99%
“…In addition, EBUS seems to be more accurate than HRCT in the assessment of the airway wall, allowing even to discriminate its particular layers. 9,10 Indeed, a very recent study showed that EBUS may be more precise than HRCT in the measurement of BWT. 13 However, it must be emphasized that the evaluation of the features of the airway wall by EBUS is usually limited to a single segmental bronchus.…”
mentioning
confidence: 99%
See 1 more Smart Citation